Evaluasi Implementasi Balanced Scorecard di Komisi Pemberantasan Korupsi - Arumastuti, Nimas Kusudiatmi; Setyaningrum, Dyah (Jurnal Manajemen Bisnis dan Keuangan, 2023)
This study aims to evaluate the balanced scorecard implementation at KPK using the Nine Steps to Success framework. This study uses a qualitative descriptive research method with a case study approach. The results of this research show that KPK has implemented eight of the nine stages in the Nine Steps to Success framework, the stage that has not been implemented is strategic initiatives. In addition, each stage needs to be improved. The suggestions from this study are to improve vision statement and increase employee knowledge related to BSC, validate customer value propositions, formulate strategic initiatives, adjust strategic goals and performance indicators, optimize STINKO applications, doing coordination related to alignment of organizational and individual performance management, and optimize monthly evaluation process.